Developing Tahrir al-Aqwal’s book using the inductive method to improve students’ ability in Arabic Grammar at Bab Al-Maghfirah Islamic College - Anita Silviana; Buhori Muslim; Badruzzaman Badruzzaman (The Department of Arabic Language Education, Pascasarjana Universitas Islam Negeri Banda Aceh of UIN Ar-Raniry Banda Aceh, Aceh, Indonesia., 2024)
This book was developed based on data that showed that students were only able to memorize grammar, but did not understand it, and thus the goals of learning grammar were not achieved. This research aims to determine the process of developing the book Tahrir al-Aqwal using the inductive method and determine the effectiveness of the book that was developed. The research methodology used is research and development using the Sugiono model which consists of ten steps. In collecting data, the researcher used observation papers, interviews, questionnaires, and tests. The population in this study was all first-grade students at Bab al-Maghfir Islamic Boarding School, numbering 95 people, and the sample was first-grade “A” students, numbering 25 people. Sample selection uses purposive sampling method. Among the most important results of the research, the book was developed through the following steps: 1). Exploring possibilities and problems, by conducting observations and interviews with grammar teachers, the results showed that the students were not able to read and understand the book and the learning objectives were not fully achieved, 2). Collect data using questionnaires to obtain students' needs, 3). Design a new textbook-style product using Microsoft Word 2013, 4). Validation of the product with experts who received a score of 98.88 from the first expert and 80 from the second and third experts,5). Improving the product by making corrections to the book title and color, as well as writing and grammar errors, 6). The product was tested on a small scale, which resulted in the book's development being effective in increasing students' abilities to learn grammar, 7). Improving the product by adding the meaning of each rule according to students’ suggestions, 8). The product was tested in large groups at Bab al-Maghfir Islamic School in the first grade, and results were obtained that learning grammar using the book that was developed was effective in improving students’ grammar comprehension abilities. This was proven by the results of the Sig t test. (2 tailed) 0.000 is smaller than 0.05 (0.000<0.05), 9). Product improvement, 10). The final product.